Failure analysis of a titanium Coriolis mass flow meter: A case of hydrogen embrittlement. (September 2020) - Santos, I.G.R.; Vacchi, G.S.; Silva, R.; Kugelmeier, C.L.; Magalhães, D.C.C.; Campesan, G.R.; Rovere, C.A.D.
Highlights: The failure of the Coriolis mass flowmeter has been investigated. Titanium alloy undergoes hydride formation due to interaction with Raney nickel. The hydride formation promoted microcracks nucleation and premature failure. The tube presented intergranular failure, typical of hydrogen embrittlement. Abstract: Titanium alloys are suitable for construction of the Coriolis mass flow meter due to their high strength to weight ratio, high thermal stability and excellent corrosion resistance. However, environments with high hydrogen content can be very harmful to titanium and its alloys, since this element may cause hydride formation and leads to hydrogen embrittlement. In this context, this paper reports on the analysis of a grade 9 titanium tube of a mass flow meter, which was performed using cyclohexanol (68%), water (2%) and Raney nickel catalyst (30%). After the active period, the flow meter was deactivated and left on standby for one year, and then reassembled on a production line, whereupon it failed prematurely. The failure was analyzed by OM, SEM, EDS, Vickers microhardness and XRD, whose results indicated that the cause was hydride embrittlement due to the chemical interaction between Raney nickel and the titanium tube during the deactivated period.